2019
DOI: 10.1016/j.ijrobp.2019.06.610
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor DNA Changes During Chemoradiation for Lung Cancer Predict Patient Outcomes

Abstract: survival. Actuarial 1-year local control was 86%; for the groups treated in 3, 5, 8 and 12 fractions, it was 90%, 83%, 85% and 71%, respectively. There were no significant differences between the groups. Actuarial survival at 1 year was 81%. Grade 3 toxicity was found in 2.9% of the patients, 9 patients having grade 3 (abdominal pain, nausea, fatigue, bile duct stenosis, and hematoma); 2 patients having grade 4 (gallbladder and gastric perforation); and one having grade 5 (hepatobiliary disorder). Conclusion: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, 79% of patients had undetectable ctDNA midway through chemoradiotherapy despite only 13% of patients experiencing a pathologic complete response, suggesting that more sensitive analysis approaches may be necessary to identify patients with persistent local disease. We recently reported that ctDNA concentration a median of 3 weeks into chemoradiotherapy for lung cancer was significantly associated with risk of disease progression and overall survival [ 137 ]. Furthermore, integrating ctDNA analysis with complementary outcome predictors may improve risk stratification [ 138 ].…”
Section: Liquid Biopsies To Monitor Cancer Treatment Responsementioning
confidence: 99%
“…However, 79% of patients had undetectable ctDNA midway through chemoradiotherapy despite only 13% of patients experiencing a pathologic complete response, suggesting that more sensitive analysis approaches may be necessary to identify patients with persistent local disease. We recently reported that ctDNA concentration a median of 3 weeks into chemoradiotherapy for lung cancer was significantly associated with risk of disease progression and overall survival [ 137 ]. Furthermore, integrating ctDNA analysis with complementary outcome predictors may improve risk stratification [ 138 ].…”
Section: Liquid Biopsies To Monitor Cancer Treatment Responsementioning
confidence: 99%